Long-read sequencing transforms the diagnosis of congenital adrenal hyperplasia: resolving pseudogene interference and structural variations - Zeng, Junfeng; Huang, Xiaoling; Li, Yanwei; Yan, Tizhen; Lou, Jiwu; Lyu, Guizhen; Li, Yanjin (Frontiers in Pediatrics, 2025)
BackgroundCongenital adrenal hyperplasia (CAH) is an autosomal recessive disorder primarily caused by defects in adrenal steroidogenesis. Conventional genetic methods struggle to resolve complex structural variations and pseudogene interference in key genes like CYP21A2. Our study will evaluate the efficacy of Long-Read Sequencing (LRS) as a comprehensive diagnostic tool for CAH, demonstrating its ability to simultaneously detect large structural variations, single nucleotide variants (SNVs), and small insertions or deletions.MethodsFour probands with clinically diagnosed CAH underwent detailed biochemical profiling, including serum 17-hydroxyprogesterone, serum sodium and serum potassium. Genomic DNA was extracted from peripheral blood and subjected to LRS using Single-Molecule Real-Time (SMRT) Technologies (Pacifc Biosciences). A targeted panel covering the CYP21A2 and HSD3B2 genes, as well as other genes related to CAH was captured. Bioinformatic analysis included alignment with Minimap2, variant calling with Sniffles2 and Medaka, and phasing analysis to resolve pseudogene interference.ResultsLRS identified compound heterozygous and homozygous variants in CYP21A2 (e.g., c.293-13C > G, c.518T > A, CH-1) and novel compound heterozygous variants in HSD3B2 (c.121G > T and c.757T > G). In combination with biochemical tests, clinical manifestations, and the ACMG guidelines, these gene mutations were the cause of the patient's disease. LRS resolved pseudogene interference and provided unambiguous cis/trans phasing.ConclusionLRS is a robust diagnostic tool for CAH, offering comprehensive detection of genetic variants, including large deletions and SNVs in both cis and trans forms. Its ability to resolve pseudogenes and structural variations positions LRS as a first-tier diagnostic tool for CAH, improving accuracy, streamlining clinical workflows and ultimately benefits patients.